Determinants of missed nursing care in Jordanian hospitals during COVID‐19 pandemic - Huthaifah Khrais; Mohammad Alsadi; Islam Oweidat; Muayyad Ahmad (Wiley, 2023)
Abstract Aim The aim of the study was to examine the effect of perceived organizational support, accountability and nurses' characteristics on missed nursing care under the impact of COVID‐19. Design A cross‐sectional design was used to describe and predict nurses' characteristics. Methods A sample of 536 Registered Nurses participated in the study from eight hospitals in different health sectors in Jordan (three public hospitals, three private hospitals and two teaching hospitals). Results Communication problems had the highest impact on missed nursing care, compared with labour resources and material resources reasons. Higher patient: nurse ratio aggravated by COVID‐19 pandemic, years of experience, satisfaction with the income, perception of accountability and organizational support were among the factors associated with the levels of missed nursing care.